MALINGERING DALAM PSIKOLOGI FORENSIK: SEBUAH TINJAUAN LITERATUR - Raihan Pamungkas; Cinta Perindu, Rahma Kurnia, Shella Amalia Khakim, Tyo Hendryan, Tugimin Supriyadi (ADISAM PUBLISHER, 2025)
Malingering is a behavior of pretending to be psychologically impaired that often appears in forensic psychology and can affect the evaluation results on which legal decisions are based. This review aims to comprehensively explore the detection of malingering in forensic psychology. The method used is a literature review by analyzing previous research from various credible sources. The results of this review are expected to increase the understanding of malingering symptoms and guide forensic professionals to handle cases accurately to support the legal process. Understanding of malingering more deeply can enhance the accuracy of assessments and fairness in the legal process